Role of Nephrostomy in poorly functioning kidneys in patients with ureteropelvic junction obstruction (UPJO) - Kumar, Vijayendra; thakur, Vinit kumar; Yadav, Ramdhani; Hasan, Zaheer; Chaubey, Digamber; Agarwal, Apurva; Prasad, Ramjee; Rahul, Sandip Kumar (Iranian Journal of Pediatric Surgery, 2019)
Introduction: Several studies have addressed the unique management challenges in poorly functioning kidneys of patients with ureteropelvic junction obstruction. Trial with percutaneous drainage of such kidneys as a guide to choose the type of surgical management would be a solution to this dilemma. We aimed to evaluate the role of percutaneous nephrostomy in treatment of poorly functioning kidneys in pediatric patients with UPJO. Materials and Methods: A prospective study was performed on patients with poorly functioning kidneys (split renal function<10% on renal dynamic scan) and unilateral ureteropelvic junction obstruction from August 2016 to January 2018. Ultrasound-guided nephrostomy was inserted for these patients. Data regarding the differential renal function and glomerular function rate (GFR) was collected before and after nephrostomy insertion. Decision regarding pyeloplasty or nephrectomy of the involved kidney was made based on changes seen in differential function and Glomerular filtration rate following the drainage. Results: Thirty three patients with unilateral UPJO with poorly functioning kidneys were treated during this period. Thirty patients had significant increase in differential function and glomerular filtration rate. These patients underwent pyeloplasty. In 2 patients, these parameters did not increase much and they underwent nephrectomy. One patient had an infected kidney which did not improve significantly on drainage and had to be removed. Of the 30 patients who had pyeloplasty, two developed obstruction after 3 months of removal of double-J stent and needed reoperation. Conclusion: Percutaneous nephrostomy in poorly functioning kidneys with ureteropelvic junction obstruction helps to identify potentially salvageable kidneys which merit pyeloplasty. Kidneys which do not improve with nephrostomy are unlikely to improve with pyeloplasty and therefore nephrectomy is done in such cases.